The Relationship Between Technological Developments and the Mental Health of Strawberry Generation Students - Javica Julianti; Suryati; Emi Puspita Dewi (al-Afkar, Journal For Islamic Studies, 2026)
This study is entitled The Relationship between Technological Development and the Mental Health of Strawberry Generation Students. This research is motivated by the rapid development of information and communication technology which has brought significant changes in various aspects of life, including the mental health of Strawberry generation students. This generation is known to be adaptive to technology, but has a tendency to be emotionally sensitive and therefore vulnerable to psychological stress. This study aims to determine the relationship between technological development and the mental health of Strawberry generation students. The research method used is a quantitative method with a correlational approach. Hypothesis testing was carried out using the Pearson Product Moment correlation test. The results showed that the calculated rvalue of 0.733 was greater than the r table of 0.227, which means there is a significant and positive relationship between technological development and the mental health of Strawberry generation students. The contribution of this research is expected to be an academic reference in the development of educational policies and psychological support services for students, especially in utilizing technology wisely to support the mental health of the younger generation.